Grasses Benefits, Diversities and Functional Roles - Almusaed, Amjad; Mohamed Salih Al-Samaraee, Sammera (IntechOpen, 2017)
This book has been prepared to embody the major and efficient applications of the different duties and roles of grasses in our life, as well as offered a solid concept for this kind of science. The book aims to illustrate various ideas, methods and how it is treated in the agronomic process for different forms of grasses in human life.